Microorganisms and the integrated conservation-intervention process ofthe renaissance mural paintings from Casas Pintadas in Évora – Know to act, act to preserve - Rosado, T (2018)
The identification of microorganisms involved in biodeterioration/biodegradation process is determinant to understand their effects on cultural assets, and furthermore, it is a crucial step to define an efficient strategy to protect monuments and artworks from microbiological recolonisation, in order to promote its preservation. The renaissance mural paintings from the garden of the Inquisition Palace in Évora, classified by UNESCO as World Heritage, were analysed in order to find the microbial population involved in the biodeterioration process, and, to assist and develop an efficient intervention, by biocides application to control the propagation of microbial communities responsible for biodegradation. The biocides tested revealed good inhibition results against the microbial communities isolated from the paintings, whose action spectrum was noticeably enlarged when the application was carried out combining two different commercial biocides. In vitro antifungal assays performed with new natural biocompounds revealed efficient inhibition capacity, suggesting the potential of these compounds to be used as a great and safe alternative to the chemical compounds usually used on cultural assets microbial treatments